All Days 2008
DOI: 10.2118/112679-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Three-Phase Flow in the Annuli During Directional UBD Operations

Abstract: Underbalanced drilling (UBD) has several advantages compared to conventional drilling. These advantages include the elimination of formation damage, higher penetration rate, reducing circulation loss and the possibility of actually producing hydrocarbons during the drilling process. UBD technology and applications have recently been applied while drilling challenging wells in Iranian fields. It is generally accepted that the success of underbalanced drilling is dependant on maintaining the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…She found that the modified Ansari's method was shown to be superior to Hasan-Kabir's because of accurately describing slug flow parameters. Mousavi et al 16 made some alterations to the modified Ansari model to correct it for Iranian reservoirs to predict the flow patterns and estimating the BHP. They validated the results with 20 wells and found out better results (less than 5%) than Ansari's method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…She found that the modified Ansari's method was shown to be superior to Hasan-Kabir's because of accurately describing slug flow parameters. Mousavi et al 16 made some alterations to the modified Ansari model to correct it for Iranian reservoirs to predict the flow patterns and estimating the BHP. They validated the results with 20 wells and found out better results (less than 5%) than Ansari's method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effective solids transport in multiphase fluids are highly dependent on the fluid flow pattern (Oyeneyin, 2015) so the flow pattern must be taken into consideration when performing cuttings transport prediction or evaluation. The gas-liquid fluid flow patterns most likely to occur for two-phase flow in an UBD wellbore are the dispersed bubble, bubble, stratified flow and slug flow patterns (Mousavi et al, 2008). Previous experimental and theoretical studies on two-phase flow in either pipes or annuli have shown that the conservation of mass, momentum and energy for two-phase gas-liquid flow are different to that of the single-phase flow and significantly dependent on the prevailing fluid flow pattern (Caetano et al, 1992;Dukler and Hubbard, 1975;Dukler and Taitel, 1986;Mukherjee 4 and Brill, 1985;Taitel and Barnea, 1990;Xiao et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In latter years, some studies have been conducted on two-phase flow hydrodynamics and flow pattern boundaries in annular geometries as well as hole cleaning. Mousavi et al (2008) presented a mechanistic model for two-phase flow in vertical wellbores. Hasan et al (2007) presented a model based on driftflux theory in order to express two-phase flow inside annulus, and compared the results with commercial software results.…”
Section: Introductionmentioning
confidence: 99%